2016
DOI: 10.1371/journal.pone.0147616
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Vitamin D Deficiency in Singapore: Its Implications to Cardiovascular Risk Factors

Abstract: ObjectiveVitamin D deficiency is a global health challenge and has been linked to type 2 diabetes and other chronic diseases. However, the relationship between vitamin D status, body composition, and cardiovascular risks has not been well characterized in Asian populations. The objectives of this study were to examine the factors associated with the low vitamin D levels in a sunny tropical region and to assess the role of vitamin D status in cardiovascular risk factors.Design and MethodsThis was a cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 40 publications
(41 reference statements)
2
27
1
Order By: Relevance
“…The prevalence of vitamin D deficiency in our study (32.9%) was lower than the prevalence (42.1%) reported in the general population (mean age: 31.5 years) of Singapore [11]. This could be partly due to the lower proportion of females (22%) in our study compared to the general population study (48%).…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…The prevalence of vitamin D deficiency in our study (32.9%) was lower than the prevalence (42.1%) reported in the general population (mean age: 31.5 years) of Singapore [11]. This could be partly due to the lower proportion of females (22%) in our study compared to the general population study (48%).…”
Section: Discussioncontrasting
confidence: 86%
“…This could be partly due to the lower proportion of females (22%) in our study compared to the general population study (48%). Females tend to have lower vitamin D levels than males, owing to the frequent use of sunscreen and higher body fat percentage [11]. There have been a few studies conducted in workplace settings on vitamin D status in Southeast Asia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among diabetes and nondiabetic groups the mean age and male:female ratio was found to be 49.76±5.21 years versus 48.52±6.03 years and 63:37 versus 66:34, respectively. The average serum 25(OH) D levels were significantly (p<0.001) low in diabetes group (9 [5,14] vs. 19 [12,28]) ng/mL (Tables 1 and 2). Compared to nondiabetes group Durgarao et al…”
Section: Resultsmentioning
confidence: 95%
“…Similar to the glycemic profile the lipid profile was also better in insufficient category which may be related to the specific pharmacotherapy of these patients. Jorde R, Grimnes G [28] reported a positive correlation between vitamin D status and HDL whereas, Xinyan Bi et al [11] found no such association but they reported a significant inverse relation between TC/HDL, LDL/HDL ratios and serum 25(OH) D levels. In this study, insignificant but negative and positive associations were reported between serum 25(OH) D levels, TC, TGs, TC/HDL ratio, AIP and HDL, respectively, among the diabetes patients (Table 4).…”
Section: Fig 1: Comparison Of Vitamin D Status Between Diabetes and mentioning
confidence: 99%